Tracing-corrected estimates of disengagement from HIV care and mortality among patients enrolling in HIV care without overt immunosuppression in Tanzania. Issue 1 (2nd January 2021) - Tymejczyk, Olga; Vo, Quynh; Kulkarni, Sarah Gorrell; Antelman, Gretchen; Boshe, Judith; Reidy, William; Parcesepe, Angela; Nash, Denis; Elul, Batya
ABSTRACT: In the era of "test and treat", it is important to understand HIV care outcomes and their determinants in patients presenting to care with early-stage disease. We surveyed 924 adults newly enrolling in HIV care at four clinics in Tanzania before the adoption of universal treatment eligibility, and collected longitudinal clinical data. Participants who defaulted from care were tracked in the community. Cumulative incidence of disengagement from care and death was estimated using competing risk methods. By 12 months after enrollment, 18.2% of patients had disengaged from care and 6.9% had died. Factors associated with disengagement included male sex (adjusted subhazard ratio [aSHR] versus female = 1.75, 95% confidence interval [CI]: 1.06–2.89), provider-initiated HIV diagnosis (aSHR versus self-referred = 1.71, 95% CI: 1.03–2.86), ineligibility for antiretroviral treatment (ART) at enrollment (aSHR versus eligibility = 2.82, 95% CI: 1.84–4.32) and increased anticipated stigma score (aSHR = 1.04 per 5-point increase, 95% CI: 1.02–1.05). Higher life satisfaction score (aSHR = 0.97 per 5-point increase, 95% CI: 0.95–0.99) and having 1–2 close friends (aSHR versus none = 0.58, 95% CI: 0.47–0.71) were protective. The findings highlight the continued importance of social environment for HIV care outcomes and the potential of universal ART eligibility to reduce HIV care attrition.